Osteochondral Autograft Transplantation/Mosaicplasty - McCoy, Brett; Miniaci, Anthony (The Journal of Knee Surgery, 2012)
The treatment of full-thickness chondral lesions remains a challenging clinical dilemma. The natural history of untreated lesions results in radiographic deterioration and suboptimal clinical outcome scores. Interventions such as marrow stimulating procedures elicit fibrocartilaginous healing. These have demonstrated some utility but concerns exist about the long-term prognosis. Mosaicplasty is an intervention that can treat full thickness defects with preservation of hyaline cartilage, which may improve the long-term outcomes. It is indicated for patients with isolated lesions between 1 and 4 cm2 in a stable knee with appropriate alignment. The procedure can be performed either open or arthroscopically depending on the surgeon's experience. Graft harvest and placement can be technically demanding. Congruency of the grafts is an essential part of the procedure. If placed in a convex location the central graft may need to be slightly longer. Graft prominence of >1 mm is poorly tolerated. Clinical results thus far have demonstrated excellent results when mosaicplasty is performed with appropriate indications.
Keywords: osteochondral; autograft; transplantation; mosaicplasty